2021
DOI: 10.3390/sym13050756
|View full text |Cite
|
Sign up to set email alerts
|

Actual Symmetry of Symmetric Molecular Adducts in the Gas Phase, Solution and in the Solid State

Abstract: This review discusses molecular adducts, whose composition allows a symmetric structure. Such adducts are popular model systems, as they are useful for analyzing the effect of structure on the property selected for study since they allow one to reduce the number of parameters. The main objectives of this discussion are to evaluate the influence of the surroundings on the symmetry of these adducts, steric hindrances within the adducts, competition between different noncovalent interactions responsible for stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 253 publications
2
5
0
Order By: Relevance
“…Photodetachment and Anionic Excited State Energy Calculations. In accordance with previous work on HPA − , 16 our calculations confirmed that the ground state geometry of the monoanion is planar, with any nonplanar geometry converging toward the planar one. In the lowest energy geometry, the acidic H atom is located in the middle of two O atoms belonging to different carboxylic groups each (see Figure 4), forming an O•••H•••O Zundel-type bond with C 2v symmetry.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Photodetachment and Anionic Excited State Energy Calculations. In accordance with previous work on HPA − , 16 our calculations confirmed that the ground state geometry of the monoanion is planar, with any nonplanar geometry converging toward the planar one. In the lowest energy geometry, the acidic H atom is located in the middle of two O atoms belonging to different carboxylic groups each (see Figure 4), forming an O•••H•••O Zundel-type bond with C 2v symmetry.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…In the case of symmetrical vicinal dicarboxylic monoanions (ortho isomers), there is an additional topic of interest concerning the location of the hydrogen atom in the intramolecular H-bond that is established between the two (equivalent) carboxylic groups. 16 A representative model system to study the symmetry of such an intramolecular Hbond is the monodeprotonated phthalic acid (HPA − , that may also be referred to as benzenedicarboxylic monoanion). In the gas phase, the intramolecular H-bond in HPA − is symmetric and hence the negative charge is equally delocalized over the two carboxylic groups.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They agree with dependences obtained for other experimental and empirical parameters [18][19][20][21][22]. More about the application of these and other correlations can be found elsewhere [23][24][25][26].…”
Section: Introductionsupporting
confidence: 87%
“…The N≡C and C•••H distances are very short. [101,102] and recently reviewed [103]. In [CN] − •••H-CN, the hydrogen bond is stronger, and the position of the proton is more symmetric.…”
Section: Proton Bound Dimers Of Cyanidementioning
confidence: 99%